Penyuluhan mengenai pencegahan dan deteksi dini kanker pada masyarakat Kota Prabumulih - Rusminan, Suly Auline; Ulfa, Maria; Fitria, Zahra; Mega, Pratia; Sandria, Sandria (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2023)
Tumors or neoplasms are abnormal solid lesions that form due to improper cell growth, and cancer is a malignant tumor. Cancer has a high potential to damage surrounding organ tissue and metastasize to other organs. Risk factors for any cancer are free radicals, secondary lifestyle, lack of healthy food, and exposure to radiation. Cancer has high morbidity and mortality. And death due to late detection, and the lack of knowledge of most people about this disease, for example, early manifestations, what to do when finding a lump on the body, tests that can be done and early detection of cancer, and others, could be the main reasons. The education is aimed at the general public to provide an overview of organ health and efforts to prevent cancer with examination and safety procedures in the era of the COVID-19 pandemic. The implementation of this outreach is able to increase public knowledge about the importance of early cancer screening. Apart from that, educating the public about cancer and early detection can increase public knowledge about cancer and self-examination for early detection procedures.